Impact of neoadjuvant chemoradiation on perioperative outcomes in patients with rectal cancer. Issue 8 (23rd March 2017) - Chapman, Brandon C.; Hosokawa, Patrick; Henderson, William; Paniccia, Alessandro; Overbey, Douglas M.; Messersmith, Wells; Lieu, Christopher; Stiegmann, Greg V.; Schulick, Richard D.; Gajdos, Csaba
Abstract : Background and Objectives: Neoadjuvant chemoradiation for rectal cancer is associated with lower local recurrence rates. The objective of this study is to assess the impact of neoadjuvant therapy on perioperative complications in patients with rectal cancer. Methods: Using the ACS‐NSQIP database (2005‐2012), a propensity score was used to match 3592 patients with rectal cancer receiving neoadjuvant therapy to 3592 patients undergoing surgery alone. The association between neoadjuvant chemoradiation and perioperative outcomes was evaluated. Results: Among all patients, overall morbidity was significantly higher in the neoadjuvant therapy group ( n = 1170, 29.9%) compared to the surgery alone ( n = 2350, 26.4%; P < 0.0001), but 30‐day mortality was lower in the neoadjuvant group ( n = 27, 0.7%) compared to the surgery alone group ( n = 112, 1.3%; P = 0.0043). However, in propensity‐matched patients, there was no difference in overall morbidity (OR 0.912, 95% CI 0.825‐1.008) or 30‐day mortality (OR 0.639, 95% CI 0.38‐1.05). Overall morbidity and 30‐day mortality were 29.3% ( n = 1054) and 0.7% ( n = 25) in the neoadjuvant group, respectively, compared to 31.3% ( n = 1124) and 1.1% ( n = 39) in the surgery alone group, respectively. Conclusion: Patients with newly diagnosed rectal cancer could be evaluated for neoadjuvant therapy prior to surgical resection without the fear of upfront therapy causing a significant increase in perioperative complications.